FIGURE 12. A–C, Acanthonyx petiverii H. Milne Edwards, 1834 in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 12. A–C, Acanthonyx petiverii H. Milne Edwards, 1834, adult male, cl 16.7 mm, cw 11.5 mm (MZUSP 40595). A, B, Habitus, dorsal and ventral views, respectively. C, Detail of the carapace, dorsal view. D, Acanthonyx dissimulatus Coelho in Coelho & Torres, 1993, holotype male, cl 20 mm, cw 13.5 mm (MZUSP 6596). Arrows indicate in (C) the first branchial lobe well-developed and in (D) the characteristic hooked setae. Photographs (A–C) by A. Pol, (D) by J. Colavite. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 28, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155